ENVIRONMENTAL IMPACTS OF GENETICALLY MODIFIED CROPS: A COMPREHENSIVE ASSESSMENT - Dr. Ashish kumar Gupta, (The Bioscan, 2025)
Genetically modified (GM) crops have emerged as one of the significant technological intervention in modern agriculture, offering potential solutions to challenges related to food security, pest control, and climate resilience. Nevertheless, their environmental effect is a topic of prevalent policy debate and scientific discussion.